Influence of vaccination of broiler chickens against Escherichia coli with live attenuated vaccine on general properties of E. coli population, IBV vaccination efficiency, and production parameters—a field experiment - Marcin Śmiałek; Joanna Kowalczyk; Andrzej Koncicki (Poultry Science, 2020)
Poultry colibacillosis has been one of the major causes behind economic losses in the poultry production; however, no effective method for its prevention has been developed so far. Vaccination against colibacillosis is capturing increasing interest. The aim of this study was to demonstrate benefits from using a live, aroA gene–deleted vaccine against colibacillosis in broiler chickens and its potential impact on reduced use of antibiotics, the efficacy of vaccination against infectious bronchitis (IB), and the structure and properties of Escherichia coli population in broilers under commercial farm conditions. In 2 experiments, carried out on 3 farms, broiler chickens of one chicken house from each farm were vaccinated against Escherichia coli (E. coli), whereas birds of other chicken houses of each farm were not vaccinated against E. coli. In experiment 1, which was carried out on 2 farms, for 3 consecutive production cycles, spray vaccination of day-old broilers against E. coli decreased the number of E. coli isolates from internal organs but not from the respiratory system in the sixth week of birds' life. In experiment 1, E. coli–vaccinated broilers did not receive the antimicrobials until 14 d after the vaccination. Escherichia coli isolates from the E. coli–vaccinated birds were more susceptible to the antimicrobials. Escherichia coli vaccination had no impact on the IB vaccination efficiency; it has reduced the mean number of days of the antimicrobial treatment and improved broiler production parameters. In experiment 2, chickens of both houses received the antimicrobials for the first 4 d of their life. Birds of chicken house 1 were vaccinated against E. coli on the ninth day of life, whereas birds of chicken house 2 were not vaccinated. In both houses, further antimicrobial usage was the same, and antimicrobials were not used until 14 d after E. coli vaccination. Similar to experiment 1, in experiment 2, vaccination decreased the number of E. coli isolates, and these isolates were more susceptible to the antimicrobials. Vaccination of broilers against E. coli should be considered in terms of routine immunoprophylaxis.